(untitled) (Texas Journal of Philology, Culture and History, 2025)
This extended analytical article explores illocution as a central communicative mechanism by synthesizing classical speech act theory, cognitive-inferential pragmatics, interactional linguistics, and social semiotics. Drawing on V.N. Vasilina’s foundational research alongside the work of Austin, Searle, Grice, Goffman, Brown & Levinson, Heritage, van Dijk, Weigand, Bhatia, Mey, Halliday, Tomasello, Clark, Sperber & Wilson, and Karaulov, the study argues that illocution is not a simple linguistic feature but a multilayered semiotic action embedded in intention, cognition, social norms, and discourse organization. The analysis demonstrates that illocution emerges from the interaction between linguistic form, mental states, inferential reasoning, cultural expectations, and interactional sequencing. The article concludes that illocution is a dynamic, negotiable, culturally situated phenomenon that requires a comprehensive interdisciplinary perspective.